Regulatory network of two circRNAs and an miRNA with their targeted genes under astilbin treatment in pulmonary fibrosis. Issue 10 (26th August 2019) - Lu, Guangping; Zhang, Jinjin; Liu, Xiangyong; Liu, Wenbo; Cao, Guohong; Lv, Changjun; Zhang, Xiaoli; Xu, Pan; Li, Minge; Song, Xiaodong
Abstract: Circular RNAs (circRNAs) are becoming new therapeutic drug targets. However, their profiles under astilbin treatment have not been reported yet. In this study, we analysed the global reprogramming of circRNA transcriptome and a regulatory network of circRNAs with their targeted genes under astilbin treatment in pulmonary fibrosis. A total of 145 circRNAs were differentially expressed in the astilbin‐treated group compared with the bleomycin‐treated group using RNA sequencing. In the bleomycin‐ and astilbin‐treated groups, 29 coexpressed circRNAs were found. The maximum number of circRNAs was distributed on chromosome two, and their length varieties were mainly within 1000 bp. Four differentially expressed circRNAs (circRNA‐662, 949, 394 and 986) were tested to validate the RNA sequencing data, and their targeted microRNAs and genes were analysed by qRT‐PCR, Western blot, Pearson correlation coefficient, a dual‐luciferase reporter system and anti‐AGO2 RNA immunoprecipitation. The results showed that circRNA‐662 and 949 can act as "miR‐29b sponges" targeting Gli2 and STAT3 to exert their functions. Our work suggests that the transcriptome complexity at the circRNA level under astilbin treatment. These circRNAs may be potential molecular targets for drug action.